(untitled) (Journal of Business and Technology (Dhaka), 2013)
This paper estimates the customer perception about supermarkets and also tries to estimate the determinants which are responsible to satisfy the customers of supermarkets in Bangladesh. For empirical estimation we use primary data from 290 respondents. The respondents are customers of selected supermarkets in Dhaka city. We use logistic regression to identify the factors. Thus age, sex, education level, monthly household income, monthly household expenditure, monthly frequency of visit to Supermarket, availability of (almost) all products and price of the products are significant predictors of satisfaction level with regard to supermarket in Bangladesh. DOI: http://dx.doi.org/10.3329/jbt.v6i2.14516 Journal of Business and Technology (Dhaka) VolVI, Issue02, (July-December, 2011) & VolVII, Issue-1 (January-June, 2012) pp.35-51